Transit potential of Kazakhstan in the Silk Road Economic Belt (International relations and international law Journal, 2018)
This article is devoted to the analysis of Kazakhstan’s transit potential in the Silk Road Economic Belt. The transit potential of the country is part of the market infrastructure that must be developed for the successful functioning of the entire economy of the country. Kazakhstan is one of the largest countries in the world that has no access to the sea, but it has the capacity and should develop its transit and transport potential. The author studies opportunities, problems and benefits of the country from use of the transit potential, shows the real need for its effective realization. In conditions of globalization of world economy transit becomes the most important condition for country’s active participation in the international trade, a factor of development of transport branch and a source of replenishment of the state budget. Effective realization of transit potential of the RK in the international transport system is promoted by the international transport corridors passing through the territory of the country diversely. Important advantage of transit through the RK territory is the stable political situation and favorable investment climate. Nowadays, transit potential of Kazakhstan is not involved fully.Key words: transit potential, transport corridors, Eurasian integration, international trade. China’s initiative, the economic belt of the Silk Road is a project that enables Kazakhstan to become a full participant in international transportation at the present time.